2022
DOI: 10.1242/jeb.243076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurotransmitter receptor antagonists on sea urchin righting behavior and tube foot motility

Abstract: Sea urchins, as echinoderms, occupy an interesting position in animal phylogeny in that they are genetically closer to vertebrates than the vast majority of all other invertebrates but have a nervous system that lacks a brain or brain-like structure. Despite this, very little is known about neurobiology of the adult sea urchin, and how the nervous system, is utilized to produced behavior. Here we investigate effects on the righting response of antagonists of ionotropic receptors for the neurotransmitters acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Strychnine, the most abundant alkaloid of SS, is highly toxic to humans and most domestic animals. Strychnine is a well-known potent antagonist of glycine receptors in the central nervous system of vertebrates and a potent blocker of various types of muscle and neuronal nicotinic acetylcholine receptors [ 23 ]. Strychnine has negligible antitumor, analgesic, and anti-inflammatory properties [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strychnine, the most abundant alkaloid of SS, is highly toxic to humans and most domestic animals. Strychnine is a well-known potent antagonist of glycine receptors in the central nervous system of vertebrates and a potent blocker of various types of muscle and neuronal nicotinic acetylcholine receptors [ 23 ]. Strychnine has negligible antitumor, analgesic, and anti-inflammatory properties [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that T4 (and to a lesser degree T3) upregulated beta-1 adrenergic receptor and the noradrenaline transporter SLC6A2 orthologs in our transcriptome analysis. While little work has been done on sea urchin adrenergic receptors, adrenergic signaling has been shown to be necessary for tube foot motility in adult sea urchins (124).…”
Section: Neuronal Signaling and Crosstalkmentioning
confidence: 99%
“…To administer the drugs, animals were immersed in tanks containing ASW, 0.1% methanol or 0.1% methanol plus haloperidol where appropriate, for 1 h and the behavioral tests were conducted in the stated solutions. A 1 h preincubation has previously been found to be sufficient to allow drug absorption and observe behavioral effects of the drug on sea urchins (McDonald et al, 2022).…”
Section: Drug Administrationmentioning
confidence: 99%
“…Righting assays were performed as in McDonald et al (2022). Briefly, animals were preincubated in test solutions for 1 h, and then were inverted and placed on their aboral side on the base of a tank containing ASW with or without the specified drugs.…”
Section: Behavioral Assays Rightingmentioning
confidence: 99%
See 1 more Smart Citation